News Coverage of Child Abuse in Nepal: Comparative Analysis of National and International Medias - Aryal, Kripa (Khwopa Journal, 2024)
This study explores media coverage of child abuse in Nepal by analysing the National and International news articles. The study employs a mixed research approach through news coverage frequency and content analysis. It has extracted 50 English news reports each from national and international news outlets that cover the issue of child abuse over the span of six years (April 2017- April 2023) The content of the news reports was grouped into appropriate fields and analyzed under the several sub-topics such as framing, type of abuse, causes, solutions, perpetrators, geography etc.This article contributes to media research studies by demonstrating the superficiality of news coverage on child abuse—which have been inadequate because of the journalistic and scholarly emphasis on objectivity—in a non-Western cultural context such as Nepal, which has hitherto received negligible attention in the field of communication. The study revealed that the Nepalese and International media seldom gave coverage to child abuse cases, and when they did, the reporting lacked substantial content. It emphasizes the need for the media to play a proactive role through in-depth analytical news promoting anti-exploitation. Since previous literature has proven the interrelation between media news coverage and action on child abuse, this study recommends more comprehensive coverage to secure public awareness and organizational policies that can promote solutions of the problem.